Desenvolvimento de uma ferramenta móvel para suportar a geração de ideias criativas utilizando Brainwriting - Lôbo, Állef Araújo (2016)
When it comes to business, academic or informal group decisions, it is necessary to use creativity and ideation to create new concepts, products or projects. To assist in the creative aspect there are several techniques that were originally applied non-electronically and block creative ability. The Brainwriting Idea Generation Technique suffers from the consequences of a discussion session limited by the physical objects that the participants have. In this way, this work proposes the adaptation of the technique of Brainwriting to an informational model of a mobile application and to make an evaluation about the use of this tool in a real context. To achieve these objectives, an analysis was made of the variants of the technique of Brainwriting, tool modeling, implementation and evaluation of the tool by the context of use in the elicitation of requirements for the new version of a system used in the Campus Quixadá UFC. From the evaluation were collected the ideas generated and opinions about their experiences with the use of the tool. These data were favorable regarding the methodology of application of the technique, having disagreements regarding problems in the visualization of the interface of the application. The result produced by this work is of great importance for the requirements engineering during the requirements elicitation process.